PENGGUNAAN ONLINE DISPUTE RESOLUTION DITINJAU DARI UNDANG-UNDANG NOMOR 30 TAHUN 1999 TENTANG ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA - Thurmudzi, Muhammad Anas; Nasution, Krisnadi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
As technology develops, new breakthroughs emerge which are considered more practical and make it easier for parties to settle business disputes out of court using Online Dispute Resolution. The Online Dispute Resolution method has not yet been regulated, meaning that there is a legal vacuum regarding the use of Online Dispute Resolution. This research is legal research. The approach used to answer this legal issue is the statute approach, which is an approach using legislation and regulations. Conceptual approach (conceptual approach) is used to examine and analyze the framework of thought, conceptual framework or theoretical basis of legal issues to be studied. Based on the results of the analysis of legal materials, it is concluded that the use of Online Dispute Resolution can be carried out where the Article 4 paragraph (3) of ADR Act stipulates that as long as it has been agreed upon by the disputing parties, dispute resolution through arbitration can occur in the form of electronic documents. Then, according to Article 5 of the ITE Act, it states that electronic information and/or electronic documents and/or their printouts are legal evidence. Even so, Online Dispute Resolution has not been able to run optimally because there are no separate regulations, therefore special arrangements regarding Online Dispute Resolution are needed to ensure legal certainty.